2016
DOI: 10.5006/2193
|View full text |Cite
|
Sign up to set email alerts
|

Materials Selection for Use in Concentrated Hydrochloric Acid

Abstract: Hydrochloric acid (HCl) is an important mineral acid with many uses, including the pickling of steel, acid treatment of oil wells, and chemical cleaning and processing. This acid is extremely corrosive and its aggressiveness can change drastically depending on its concentration, the temperature, and contamination by oxidizing impurities. One of the most commonly encountered oxidizing impurities is the ferric ion. In general, stainless steels cannot tolerate aggressive HCl solutions, hence the need to use corro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
4
21
0
Order By: Relevance
“…The results are in consensus with the weight loss data [4]. Recently, Mishra et al [10] demonstrated the role of alloying elements on the corrosion performance of various Ni-Cr-Mo (W) alloys in aggressive chloride environment which can also be simulated as a critical crevice solution.…”
Section: Introductionsupporting
confidence: 74%
“…The results are in consensus with the weight loss data [4]. Recently, Mishra et al [10] demonstrated the role of alloying elements on the corrosion performance of various Ni-Cr-Mo (W) alloys in aggressive chloride environment which can also be simulated as a critical crevice solution.…”
Section: Introductionsupporting
confidence: 74%
“…For applications in HF and H 2 SO 4 , Fe-and Ni-based alloys containing Cu exhibit an enhanced corrosion resistance performance [7][8][9][10][11][12]. In Crrich alloys, Cr primarily forms a passive film of Cr 2 O 3 on the surface, thereby imparting better passivation properties [6,[13][14][15][16]. Molybdenum and tungsten are known to inhibit localized corrosion by oxide formation within the pit, thereby retarding the pit/crevice growth [6,[13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study [6,13] performed on a wide range of corrosion-resistant Ni-Cr-Mo and Ni-Cr-Mo-W alloys in various acidic solutions suggested that Mo (or Mo and W) forms a protective oxide in low pH-reducing acids (like HCl, H 2 SO 4 and H 3 PO 4 ), responsible for an enhanced corrosion resistance performance in Mo-rich alloys, Available online at http://link.springer.com/journal/40195 & Ajit Mishra ajitosu@gmail.com…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also called muriatic acid, it is used for cleaning surfaces of various metals and alloys, including steel, especially to remove scales, rust and mineral deposits. In general, HCl used is for chemical cleaning/pickling of steel, reduction of ores and processing, industrial preparation of chlorine and chlorides, acid treatment of oil and gas wells and in food processing [1]. However, HCl is known for its high corrosivity, and depending on temperature under which operation is carried out and the concentration of the acid used, it can rather be aggressive to and corrode the surfaces meant to be cleaned.…”
Section: Introductionmentioning
confidence: 99%